An Empirical Analysis of The Inward Export Structure of Mongolia’s Higher Education - Tu, Eerdemu; Sukhbaatar, J. (International Journal of Accounting and Economics Studies, 2025)
This study aims to examine the inward export structure of higher education services in Mongolia. The study emphasises the impact of different components on the performance of the inward export of higher education services in Mongolia. The research adopts a quantitative research design using correlation and modeling analysis methods. Data were collected from the Mongolian Ministry of Education and the China Education Statistical Yearbook. This study divides Mongolia’s inward exporting countries of higher education services into two groups, China and non-China, and examines the relationship between Mongolia’s inward export performance of higher education services and its inward export volume to China and to non-China countries. The result revealed that the number of international students in Mongolian higher education is highly positively correlated with the number of international students from China, and medium-strength positively correlated with non-China countries. The regression equation between the number of foreign students studying in Mongolian higher education and the number of students from China shows a significant positive impact. The study also shows that COVID-19 had a significant negative impact on the total number of foreign students in Mongolia. This study examines the inward export structure of Mongolia’s higher education service trade and provides valuable reference directions for improving the inward export performance of Mongolia’s higher education services. The inward export structure of Mongolia’s higher education service trade was analyzed, and the impact of COVID-19 is included.